Legal Regulation of Egg Freezing for Single Women: The Game Between Reproductive Rights and Ethics - She, Yuyang (Asia Pacific Economic and Management Review, 2025)
With the development of assisted reproductive technology, the issue of single women freezing eggs has sparked widespread controversy between reproductive rights and ethics. The verdict of China’s first "single woman egg freezing case" highlights the current legal restrictions on single women’s egg freezing, and also leaves room for future policy adjustments. As a fundamental human right, the right to reproduction should be attributed to personality rights rather than identity rights. The demand of single women for egg freezing conflicts with traditional ethical concepts, mainly revolving around issues such as intergenerational equality, the weakening of traditional family values, and possible illegal transactions. This article discusses ethical controversies and proposes legal regulatory pathways, calling on society to provide space for diversified reproductive choices while respecting traditional ethics.